Socio-cognitive risk factors of conventional substance abuse - Uba, Ikechukwu; Yaacob, Siti Nor; Abu Talib, Mansor; Abdullah, Rohani; Mofrad, Sakineh (Asian Economic and Social Society, 2013)
This study examined the socio-cognitive risk factors of conventional substance abuse among adolescents. The research utilized a set of self-report instruments on a sample of 352 high school students (13 to 18 years), from Lagos, Nigeria. The measures assessed substance abuse, peer substance use, stress, depression, self-esteem and religiosity. The result identified low self-esteem as the unique predictor of substance abuse among adolescents. Recommendations of the study emphasized the importance of high self-esteem among adolescents. Future research may examine other variables not assessed in the study.